Effect of training and motivations on employee performance of Tribhuvan University - Neupane, Bashu; Baral, Puskar (NCC Journal, 2022)
The primary goal of the study is to determine how training and motivation affect the performance of T.U. workers in the Kathmandu Valley. The data is gathered using the self-structured questionnaires. The study’s respondents are the 54 T.U. personnel who are located in the Kathmandu Valley. The primary data is gathered using a 5-point Likert scale. The reliability and validity of the gathered data are evaluated using the Cronbach alpha. The independent variable could be able to explain the dependent variable, according to alpha of 0.625. The features of the data are described using descriptive statistics. To investigate cause and effect, regression analysis is utilized. The study significantly improves the performance, training, and motivation of Tribhuvan University staff members who operate in the Kathmandu Valley.